Multiscale Invasion Assay for Probing Macrophage Response to Gram-Negative Bacteria - Wodzanowski, Kimberly A.; Caplan, Jeffrey L.; Kloxin, April M.; Grimes, Catherine L. (Frontiers in Chemistry, 2022)
The immune system is a complex network of various cellular components that must differentiate between pathogenic bacteria and the commensal bacteria of the human microbiome, where misrecognition is linked to inflammatory disorders. Fragments of bacterial cell wall peptidoglycan bind to pattern recognition receptors within macrophages, leading to immune activation. To study this complex process, a methodology to remodel and label the bacterial cell wall of two different species of bacteria was established using copper (I) catalyzed azide-alkyne cycloaddition (CuAAC) and strain-promoted azide-alkyne cycloaddition (SPAAC). Additionally, an approach for three-dimensional (3D) culture of human macrophages and their invasion with relevant bacteria in a well-defined hydrogel-based synthetic matrix inspired by the microenvironment of the gut was established. Workflows were developed for human monocyte encapsulation and differentiation into macrophages in 3D culture with high viability. Bacteria invaded into macrophages permitted in situ peptidoglycan labeling. Macrophages exhibited biologically-relevant cytokine release in response to bacteria. This molecularly engineered, multi-dimensional bacteria-macrophage co-culture system will prove useful in future studies to observe immunostimulatory, bacterial fragment production and localization in the cell at the carbohydrate level for insights into how the immune system properly senses bacteria.